Post-traumatic growth experience with kinship hematopoietic stem cells transplantation in patients with aplastic anemia: A qualitative study. - Xinrui Huang; Yan Xu; Yue Pan; Menghua Ye; Ting Liu; Min Xu (PLoS ONE)
Background A Hematopoietic stem cell transplant is the only way to cure aplastic anemia. Selection of relative donors can improve the chance of transplantation. However, the treatment of kinship transplantation and disease both bring traumatic experience to patients. Understanding the specific psychological changes in a patient's post-traumatic growth experience can help improve the quality of care. Objective The purpose of this study is to explore the post-traumatic growth experience in patients with aplastic anemia received kinship hematopoietic stem cell transplantation. Methods A homogeneous small-sample strategy to select aplastic anemia kinship hematopoietic stem cell transplantation patients and medical staff in the Department of Hematology of a tertiary hospital in China as study participants. Face-to-face semi-structured interview method was used to collect verbal and nonverbal data. Data analysis started from a single case, and after completing the detailed analysis of the first text, the next text was followed until sufficiently rich research information was obtained. Interpretative phenomenological analysis was used to collect verbal and nonverbal data through purposive sampling. Results By analyzing the interview data on the post-traumatic growth experiences of six aplastic anemia kinship hematopoietic stem cell transplant patients and three medical staff, four themes and nine sub-themes were developed. Conclusions This study reveals the specific process of posttraumatic growth in patients with aplastic anemia kinship hematopoietic stem cell transplantation. Clinical workers can provide targeted psychological interventions based on the stages of patients' posttraumatic growth in order to improve the status of post-traumatic growth and quality of life of patients with aplastic anemia kinship hematopoietic stem cell transplantation.